Does Early Child Care Help or Hurt Children's Development? - Christina Felfe; Rafael Lalive (Institute for the Study of Labor (IZA), 2014)
More children than ever attend center-based care early in life. We study whether children who attend center-based care before age 3 have better or worse language and motor skills, socio-emotional maturity, and school readiness just before entering primary school. In data covering about 36,000 children in one West German state, we use a marginal treatment effects framework to show how causal effects vary with observed characteristics of children, parents, and care centers and with unobserved preferences for center-based care. Early center-based care benefits children with less educated mothers or foreign parents. Benefits increase when parents have a preference for center-based care. Centers with small playgroups and with experienced, trained, or full-time working staff produce the best effects. A modest expansion of the number of places in early care centers improves children's development, whereas a strong expansion has no significant effects.
Keywords: J13; I21; I38; 330; child care; child development; marginal treatment effects